Electroencephalography Microstate Alterations in Otogenic Vertigo: A Potential Disease Marker - Li, Yi-Ni; Lu, Wen; Li, Jie; Li, Ming-Xian; Fang, Jia; Xu, Tao; Yuan, Ti-Fei; Qian, Di; Shi, Hai-Bo; Yin, Shan-Kai (Frontiers in Aging Neuroscience, 2022)
Objectives: A huge population, especially the elderly, suffers from otogenic vertigo. However, the multi-modal vestibular network changes secondary to periphery vestibular dysfunctions have not been fully elucidated. We aim to identify potential microstate electroencephalography (EEG) signatures for otogenic vertigo in this study. Methods: Patients with recurrent otogenic vertigo and age-matched healthy adults were recruited. We performed 256 electrodes high-density EEG recording of all participants at resting state. Neuropsychological questionnaires and vestibular function tests were taken as a measurement of patients’ symptoms and severity. We clustered microstates into 4 classes (A, B, C, and D) and identified the dynamic and syntax alterations of them. These features were further fed into a support vector machine (SVM) classifier to identify microstate signatures for vertigo. Results: We compared 40 patients to 45 healthy adults, finding an increase in the duration of Microstate A, and both the occurrence and time coverage of Microstate D. The coverage and occurrence of Microstate C decreased significantly and the probabilities of nonrandom transitions between Microstate A and D as well as Microstate B and C also changed. The SVM classifier built based on these features got a balanced accuracy of 0.79 with a sensitivity of 0.78 and a specificity of 0.8 to distinguish the patients. Conclusion: There are several temporal dynamic alterations of EEG microstates in otogenic vertigo patients, especially in Microstate D, reflecting the underlying process of visual-vestibular reorganization and attention redistribution. This neurophysiological signature of microstates could be used to identify vertigo patients in the future.